2014
DOI: 10.1002/2013wr014087
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal precipitation patterns along pathways of South American low-level jets and aerial rivers

Abstract: [1] We study the seasonal dynamics of the eastern Pacific (CHOCO) and Caribbean lowlevel jets (LLJ), and aerial rivers (AR) acting on tropical and subtropical South America. Using the ERA-Interim reanalysis , we show that the convergence of both LLJs over the eastern Pacific-western Colombia contributes to the explanation of the region's world-record rainfall. Diverse variables involved in the transport and storage of moisture permit the identification of an AR over northern South America involving a midtropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
190
0
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(226 citation statements)
references
References 71 publications
(97 reference statements)
11
190
0
16
Order By: Relevance
“…On the other hand, the process variables (PRC and EVP) are the most complex in the region HPREC= 0.76 and HEVP= 0.71. This result confirms the diversity of factors that make part of the hydro-climatic variance at interannual timescale, thus reflecting the implicit complexity of the linkages between these two processes over TropSA [44,46,59,[70][71][72]. The high entropy of EVP can be also explained in terms of the multivariate influence of water and energy fluxes in TropSA [22,47,73].…”
Section: Svd Noise Reduction and Entropysupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, the process variables (PRC and EVP) are the most complex in the region HPREC= 0.76 and HEVP= 0.71. This result confirms the diversity of factors that make part of the hydro-climatic variance at interannual timescale, thus reflecting the implicit complexity of the linkages between these two processes over TropSA [44,46,59,[70][71][72]. The high entropy of EVP can be also explained in terms of the multivariate influence of water and energy fluxes in TropSA [22,47,73].…”
Section: Svd Noise Reduction and Entropysupporting
confidence: 71%
“…For the high ENSO-related group, this resilience is basically the robust memory in time of the interactions among state and process variables favored by the SST-pattern presented in the figure 8A. It is worth recalling that, over the spatial domain of TropSA, the maximum connectivity of the variables of this high ENSO-related group is representative in regions of significant correlations shown in Figure 5 whose main action core is the Amazon rainforest and the north-west zone strongly influenced by the Choco Low-Level Jet [72]. At structural level, a large part of this connectivity resides in the soil moisture (VSW) as shown in Figure 12 for the linear and non-linear metrics.…”
mentioning
confidence: 80%
“…However, the interaction of E and Θ share more covariance than P-Θ in the leading mode. Such a strong covariability between soil moisture (Θ) and evaporation (E) reinforces the idea that droughts are also associated with LAFs at local scales, and with teleconnections at larger scales in TropSA [23,68,69].…”
Section: Maximum Covariance Analysis Among Variables and Strength Of supporting
confidence: 67%
“…Figure 4b,c shows the typical spatial pattern of the highest-related ENSO modes corresponding to the interaction between evaporation (E) and soil moisture (Θ). The core of this pattern is located in the Amazon River basin and is connected to the Magdalena-Cauca River basin and the western Pacific coast of Colombia where the Choco Jet has a strong effect on the hydroclimate variability [68] ( Figure 4B,C). Some regions of the Orinoco and Tocantins River basins do not show statistically significant values (p < 0.01) under this mode.…”
Section: Maximum Covariance Analysis Among Variables and Strength Of mentioning
confidence: 99%
“…Among these processes are evaporation, which induce the increase of the amount of water vapor in the atmosphere. In addition, various processes linked to atmospheric dynamics, such as the development of the Caribbean and Choco lowlevel jets (CLLJ and CJ), are fundamental in the transport of water vapor from oceanic masses to continental masses [1,2,3,4]. Duran-Quesada et al [1], not only identified the major sources of atmospheric moisture to CAM, but also perform a spatial analysis of the influence of low level jets on precipitation in the region and its interannual variability associated with phenomena such as El Niño-Southern Oscillation (ENSO), finding a strong response of moisture transport patterns to this phenomenon.…”
Section: Introductionmentioning
confidence: 99%